Functional Analysis of the FZF1 Genes of Saccharomyces uvarum - Liu, Xiaozhen; Liu, Xiaoping; Zhang, Zhiming; Sang, Ming; Sun, Xiaodong; He, Chengzhong; Xin, Peiyao; Zhang, Hanyao (Frontiers in Microbiology, 2018)
Being a sister species of Saccharomyces cerevisiae, Saccharomyces uvarum shows great potential regarding the future of the wine industry. The sulfite tolerance of most S. uvarum strains is poor, however. This is a major flaw that limits its utility in the wine industry. In S. cerevisiae, FZF1 plays a positive role in the transcription of SSU1, which encodes a sulfite efflux transport protein that is critical for sulfite tolerance. Although FZF1 has previously been shown to play a role in sulfite tolerance in S. uvarum, there is little information about its action mechanism. To assess the function of FZF1, two over-expression vectors that contained different FZF1 genes, and one FZF1 silencing vector, were constructed and introduced into a sulfite-tolerant S. uvarum strain using electroporation. In addition, an FZF1-deletion strain was constructed. Both of the FZF1-over-expressing strains showed an elevated tolerance to sulfite, and the FZF1-deletion strain showed the opposite effect. Repression of FZF1 transcription failed, however, presumably due to the lack of alleles of DCR1 and AGO. The qRT-PCR analysis was used to examine changes in transcription in the strains. Surprisingly, neither over-expressing strain promoted SSU1 transcription, although MET4 and HAL4 transcripts significantly increased in both sulfite-tolerance increased strains. We conclude that FZF1 plays a different role in the sulfite tolerance of S. uvarum compared to its role in S. cerevisiae.